1966
DOI: 10.1017/s0080456800023668
|View full text |Cite
|
Sign up to set email alerts
|

XIV.—Some Lower Carboniferous Fructifications from Berwickshire, together with a Theoretical Account of the Evolution of Ovules, Cupules, and Carpels

Abstract: SynopsisTwo new species of petrified seedsEosperma edromense, andAnasperma burnensegen. et sp. nov. are described from the Cementstone Group of Berwickshire.Anaspermashows that the anatropous condition existed among Palæozoic ovules; it has a single integument with two lateral apical lobes.Rachides ofStauropteris berwickensissp. nov. and associated megasporangia are also described.An account is given of the theory of the telomic origin of the first ovular integument. The second (outer) integument in Angiosperm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

1967
1967
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 48 publications
0
58
0
Order By: Relevance
“…Many earlier discussions of the origin of angiosperms concluded that angiosperms were ''derived from'' seed ferns (e.g., Long 1966, Cronquist 1968, Takhtajan 1969. From a cladistic viewpoint, such statements are not very informative, since all phylogenetic analyses of living and fossil seed plants have indicated that ''seed ferns'' are a paraphyletic grade made up of lines that are basal to more derived groups (Crane 1985, Doyle and Donoghue 1986, Rothwell and Serbet 1994, Doyle 1996.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many earlier discussions of the origin of angiosperms concluded that angiosperms were ''derived from'' seed ferns (e.g., Long 1966, Cronquist 1968, Takhtajan 1969. From a cladistic viewpoint, such statements are not very informative, since all phylogenetic analyses of living and fossil seed plants have indicated that ''seed ferns'' are a paraphyletic grade made up of lines that are basal to more derived groups (Crane 1985, Doyle and Donoghue 1986, Rothwell and Serbet 1994, Doyle 1996.…”
mentioning
confidence: 99%
“…Similar problems affect Long's (1966) derivation of the carpel from the lobate, dichotomously organized cupule of Carboniferous seed ferns. On recognizing the problem of the bitegmic ovule, Long was forced to postulate that the second integument arose de novo as an outgrowth of the first.…”
mentioning
confidence: 99%
“…Such a hypodermis has been occasionally mentioned in other representatives of the genus. In S. berwickensis, from both volcanic and fluviatile environments (Scott and Galtier, 1996) the occurrence of this tissue was suggested but not illustrated by Long (1966). Cichan and Taylor (1982) mentioned a narrow hypodermis in the main axis of S. biseriata.…”
Section: Ecological Adaptationmentioning
confidence: 98%
“…is still unknown. The genus currently includes four species: the homosporous S. oldhamia Binney (1872) is the type-species; it shows a quadriseriate branching pattern; S. burntslandica (Bertand, 1909) and S. berwickensis (Long, 1966) have also a quadriseriate branching pattern but are heterosporous. The fourth species, S. biseriata (Cichan and Taylor, 1982), exhibits a biseriate branching pattern; its reproductive biology is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, among the earliest known conifers, the Permian genera Ernestiodendron and Walchiostrobus included some species with erect and some with reflexed ovules (Florin, 1951). Even earlier still, in the Lower Carboniferous, while most of the pteridosperm ovules so far discovered were orthotropous, one was campylotropous-Camptosperma and another was anatropous-Anasperma (Long, 1966). Throughout the hundreds of millions of years of ovule evolution, therefore, the overall shape of the ovule appears to have mattered scarcely at all What was important in Carboniferous times was the number of envelopes round the nucellus, and this still seems to be true of angiosperm ovules today.…”
mentioning
confidence: 99%